Care sharing for people with HIV/AIDS: a look targeted at young adults - Bruna Coelho; Betina Hörner Schlindwein Meirelles
ABSTRACT Objective: To understand the care sharing for people living with HIV/AIDS, especially young adults, as well as the structuring of the line of care in the capital of Santa Catarina. Method: Qualitative research, anchored by theory based on data collected in the Health Care Network of Florianópolis, totaling 19 participants distributed between two sample groups. The data collection and analysis were concomitant, with comparative analysis method. Results: The municipality has been transitioning in the health care model for people with HIV/AIDS, especially young adults, whose care is shared within the Health Care Network. Final considerations: In the municipality, there is the inclusion of management of HIV in primary health care services along with the establishment of a more resolutive care model. Thus, the care of this population is shared in different points of the health care network.